2014
DOI: 10.1111/ejh.12250
|View full text |Cite
|
Sign up to set email alerts
|

Management of erythropoiesis: cross‐sectional study of the relationships between erythropoiesis and nutrition, physical features, and adiponectin in 3519 Japanese people

Abstract: Although erythroid abnormalities (anemia and polycythemia) are commonly observed pathological conditions, not much information about borderline abnormalities is available. In this study, a cross-sectional study to analyze the relationships between erythropoiesis and nutrition, physical features, and laboratory test findings was conducted in middle-aged and older men and women. The study included 3519 Japanese people (1579 men and 1940 women), age 40 years and over. Analysis of variance showed that the group wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 15 publications
4
17
0
Order By: Relevance
“…This is not the first reported observation of an association between total protein level and anemia. The finding that an elevated serum protein level is predictive of anemia in women is in accordance with the study by Kohno et al [25]. In their study, total protein was found to negatively affect erythropoiesis in both men and women.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is not the first reported observation of an association between total protein level and anemia. The finding that an elevated serum protein level is predictive of anemia in women is in accordance with the study by Kohno et al [25]. In their study, total protein was found to negatively affect erythropoiesis in both men and women.…”
Section: Discussionsupporting
confidence: 91%
“…shown to be involved in hematopoiesis [25]. In a recent cross-sectional study of 3519 Japanese subjects, low triglycerides and high total protein levels were significant factors that affected erythropoiesis [25]. In their study a negative correlation between triglycerides and adiponectin was shown.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a small-scale cohort study, high serum adiponectin levels were observed in postmenopausal women with mild anemia [9]. In addition, our previous large-scale cohort study of middle-aged and elderly individuals was the first to show that adiponectin, when highly expressed in serum, decrease red blood cell (RBC) counts in men as well as in women [10]. Recently, Lewerin et al reported that high adiponectin levels were associated with low blood hemoglobin (Hb) levels in elderly men in a large cohort study [11].…”
Section: Introductionmentioning
confidence: 99%
“…A study suggests action of adiponectin on proliferation of hematopoietic stem cells by activating the receptor AdipoR1 in those cells (DIMASCIO et al, 2007). Moreover, studies of Matsubara et al (2004) and Kohno et al (2014) show a suppressive effect of adiponectin on bone marrow in vivo in humans. In this study, there was correlation between adiponectin and count of red blood cells and platelets suggesting a proliferative effect of adiponectin on hematopoiesis in healthy female dogs.…”
Section: Discussionmentioning
confidence: 99%